Contemporary Basque Cinema: Online, Elsewhere and Otherwise Engaged. Issue 10 (November 2016) - Stone, Rob; Rodríguez, María Pilar
Abstract : Basque cinema is and always has been a vital medium for the examination and perpetuation of Basque identity. It is as buffeted by civil war and social change as it is by new media technologies and linguistic, cultural, propagandist and industrial imperatives. It may represent a small nation, but the interwoven history, politics and art of Basque cinema is founded upon immense ambition. This article establishes the criteria for the definition and classification of an open, plural and mixed Basque cinema that functions as a focal point for many issues of topical and enduring debate. These include questions of language in relation to identity, the cultural expression of diasporic communities, the notion of nationalism in relation to cultural expression, the propagation of tradition and the value of aesthetic and technological innovation, as well as the importance of funding for the arts in relation to nation-building (and the possibility of that funding being used to create subversive works). It concludes with a consideration of the function of the cinema within a specific community and region that points to comparative associations with the cinemas of other nations.